EU–ASEAN Green Bond Policies: A Legal Comparative Review and Their Implications for Sustainable Finance Development in ASEAN - Dung, Nguyen Phuong; Hanh, Vu Truc (Universitas Islam Indonesia, 2025)
Climate change presents an urgent and far-reaching global challenge, and current mitigation efforts remain insufficient to limit global temperature rise to the 1.5°C threshold set under the Paris Agreement. Although Southeast Asia contributes only modestly to global greenhouse gas emissions, the region faces disproportionately severe climate risks stemming from rapid population growth, accelerating industrialization, and continued dependence on fossil fuels. In this context, green finance—particularly the issuance of green bonds—has emerged as a pivotal instrument for mobilizing capital toward environmentally sustainable development and supporting the achievement of the Sustainable Development Goals (SDGs). The European Union has made notable progress in constructing a comprehensive and coherent regulatory framework for sustainable finance, exemplified by the EU Green Bond Standard, the EU Taxonomy, and related disclosure requirements. These mechanisms collectively enhance market integrity, promote investor confidence, and ensure the environmental credibility of financial instruments. By contrast, ASEAN member states confront persistent challenges, including regulatory fragmentation, limited institutional capacity, and underdeveloped legal infrastructures, which hinder the effective deployment and scaling of green bonds across the region. This article conducts a comparative legal and policy analysis of green bond frameworks in the EU and ASEAN, examining their respective regulatory architecture, implementation mechanisms, and degree of alignment with international standards. Through this comparison, the study identifies critical gaps within ASEAN’s regulatory landscape and highlights opportunities for strengthening sustainable finance governance. The article ultimately recommends the adoption of harmonized taxonomies, the formulation of coherent national policies, and the enhancement of regional cooperation as essential strategies for advancing a robust and credible green bond market in the ASEAN region.